Implementation of an Accounting Information System Using a Website to Support the Performance of the Palasari Village Government, Ujung Jaya District, Sumedang Regency - dony waluya firdaus (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2021)
The purpose of this Community Service in Palasari Village, Ujung Jaya District, Sumedang Regency is the implementation of a web-based accounting information system. The assistance of the Palasari village community uses two schemes in the implementation of the accounting information system, namely the first scheme for general WEB introduction and the second scheme for WEB maintenance. The methodology uses a descriptive approach, surveys, interviews, and implementation of a web-based accounting information system using a content management system. The assistance of the Palasari village community in the implementation of a web-based accounting information system was carried out by video conferencing using zoom media. Based on the results of the questionnaire, community service was considered quite good and village officials needed continuous training.